IMPROVING STUDENTSâ€™ SPEAKING ABILITY IN GIVING ARGUMENTS THROUGH â€œI SOLVEâ€ TECHNIQUE - Nurfajriyani, Atikah Suri; Apriliaswati, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted on the eleventh grade students of SMA Muhammadiyah 1 Pontianak in academic year 2016/2017. The research was conducted to improve studentsâ€™ speaking ability in giving arguments. The method of this research was classroom action research. The tools of data collecting were observation sheet and field note. This research was done in three cycles. The result of data analysis showed that the studentsâ€™ speaking ability were improved. â€œI SOLVEâ€ technique could reduce studentsâ€™ pauses and hesitation, improved studentsâ€™ appropriate use of words to express opinion, improved studentsâ€™ correct use of present tense or future tense, and improved studentsâ€™ interaction in argumentative speaking. Those improvements also supported by the studentsâ€™ speaking ability rate. In the first cycle their average score was 45.4, 71.5 in the second cycle, and improved to 83.6 in the third cycle. Thus, it can be concluded that â€œI SOLVEâ€ technique did improve studentsâ€™ speaking ability in giving arguments. Teachers could use â€œI SOLVEâ€ technique as an alternative technique in teaching speaking. However, they should manage the time carefully so that they will have enough time to evaluate and give feedback to the studentsâ€™ speaking.Â Keywords: Studentsâ€™ Speaking Ability, Argumentative Speaking, â€œI SOLVEâ€ TechniqueÂ